NUMERICAL-SOLUTION OF AN ALLOY SOLIDIFICATION PROBLEM - Crowley, A; Ockendon, J (1979)
A model is described for the solidification of a dilute alloy, in which the equations of heat and mass transfer are coupled through the conditions at the moving phase boundary. The equations are rewritten in conservation form, and this suggests a method for finding numerical solutions without explicitly tracking the phase boundary. Although the method cannot be rigorously justified, it gives results which compare well with known analytical solutions in a situation where good agreement might not have been expected. © 1979.